The Role of Microfinance in Reducing Child Labour in Nepal - Karna, Poonam Kumari Labh (Darul Yasin Al Sys, 2025)
In Nepal, child labor is still a major problem that is fueled by ingrained societal norms, limited educational opportunities, and economic hardship. This study examines how microfinance might be used to address the underlying reasons of child labor in order to decrease it. In order to raise household income, lessen economic vulnerability, and enhance access to education, microfinance institutions (MFIs) provide financial services such microloans, savings accounts, and insurance products. Microfinance and child labor, however, have a complicated relationship with both beneficial and detrimental effects. Microfinance can help reduce poverty and the need for child labor, but it can also unintentionally make child labor more in demand in family-run businesses. This study investigates how microfinance affects household income, educational opportunities, and awareness-raising initiatives in Nepal by drawing on case studies and current literature. According to the research, microfinance can considerably lower child labor if financial products are properly planned and executed and paired with more extensive socioeconomic initiatives. Developing kid-sensitive financial products, incorporating awareness programs, and working with governmental and non-governmental organizations to address the root causes of child labor are some of the main recommendations. In the end, microfinance can be a potent instrument in building a future where all Nepali children have the chance to learn, develop, and prosper, even while it cannot end child labor on its own.